Purification and characterization of four benzophenone derivatives from Mangifera indica L. leaves and their antioxidant, immunosuppressive and α-glucosidase inhibitory activities. (January 2019) - Gu, Chengzhen; Yang, Meilian; Zhou, Zhihong; Khan, Afsar; Cao, Jianxin; Cheng, Guiguang
Graphical abstract: Highlights: Isolation and bioactivity screening of four benzophenones from M. indica L. leaves were performed. Two new benzophenone glycosides were identified from M. indica . The new compounds have inhibitory effect on Con A-induced splenocytes proliferation. Both Mangiferin and norathyriol had a good α -glucosidase inhibitory activity. The mango plant can be considered as a promising source of functional agents. Abstract: The aim of the present study was to isolate phytochemicals from Mangifera indica L. leaves and to screen their bioactivities. Four benzophenone derivatives were isolated and characterized, two of which were new compounds, namely manindicins A and B. All the four compounds significantly inhibited the cellular ROS amount of H2 O2 -induced HepG2 cells. Stimulation index of spleen cells showed that manindicins A and B had a good and similar immunosuppressive activity, while mangiferin and norathyriol exhibited relatively weaker activity. Norathyriol showed the strongest inhibitory effect on α-glucosidase with an IC50 of 4.22 ± 0.19 μg/mL, which was lower than that of acarbose (16.28 ± 1.22 μg/mL). However, the manindicins A and B had weak inhibition of α-glucosidase. The present work suggests that M. indica leaves can be used potentially as functional-food supplement for improving human health.